2013
DOI: 10.3109/13693786.2012.737031
|View full text |Cite
|
Sign up to set email alerts
|

The non-mammalian hostGalleria mellonellacan be used to study the virulence of the fungal pathogenCandida tropicalisand the efficacy of antifungal drugs during infection by this pathogenic yeast

Abstract: Although Candida tropicalis is a frequent cause of invasive fungal diseases, its interaction with the host remains poorly studied. Galleria mellonella is a Lepidoptera model which offers a useful tool to study virulence of different microorganisms and drug efficacy. In this work we investigated the virulence of C. tropicalis in G. mellonella at different temperatures and the efficacy of antifungal drugs in this infection model. When larvae were infected with yeast inocula suspensions of different concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
71
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(87 citation statements)
references
References 39 publications
7
71
1
Order By: Relevance
“…In these environments, C. albicans was able to develop from the yeast to hyphal form (Huang 2012;Mayer et al 2013). Our data are consistent with previous research reporting the formation of pseudomycelium by Candida tropicalis mycothallus when hemocyte numbers were reduced in G. mellonella (Mesa-Arango et al 2013). Some reports suggested that insect blood cells were constantly regenerated and kept dynamically changing.…”
Section: Discussionsupporting
confidence: 83%
“…In these environments, C. albicans was able to develop from the yeast to hyphal form (Huang 2012;Mayer et al 2013). Our data are consistent with previous research reporting the formation of pseudomycelium by Candida tropicalis mycothallus when hemocyte numbers were reduced in G. mellonella (Mesa-Arango et al 2013). Some reports suggested that insect blood cells were constantly regenerated and kept dynamically changing.…”
Section: Discussionsupporting
confidence: 83%
“…Galleria mellonella larvae were infected with an inoculum of 2 ϫ 10 6 CFU/larva when strain ATCC 750, CL-6835, or TP-13650 was used. An inoculum of 4 ϫ 10 6 CFU/larva was used for ATCC 200956, since this strain shows reduced virulence in this model (37). In all cases, 80% of infected and untreated larvae died between the 3rd and 4th day postinfection.…”
Section: Fig 1 Positions Of the Point Mutations Of Candida Tropicalismentioning
confidence: 99%
“…Among these, Galleria mellonella presents certain benefits in comparison with other nonmammalian models of infection (31). Previous studies have documented that G. mellonella is a valid model for the evaluation of microbial virulence and/or the efficacies of different antimicrobial agents against infections caused by different bacteria and fungi (32)(33)(34)(35)(36)(37)(38).…”
mentioning
confidence: 99%
“…Wax moth larvae killing assays were carried out as described previously. 24,25 Briefly, groups of 10 larvae (0.3-0.5 g, Alcotan S.L., Valencia, Spain) were inoculated with 10 mL of a 10 7 conidia/ml suspension in PBS into the haemocoel, so the final inoculum in each group was 10 5 conidia per larva. Mixed infected larvae were inoculated with A. fumigatus and A. lentulus (ratio 1:1) to a final concentration of 10 5 conidia per larvae.…”
Section: Murine Infectionsmentioning
confidence: 99%